Survei Tingkat Kesulitan Siswa dalam Pembelajaran Senam Lantai Guling Depan Se-Dabin Talang Kabupaten Tegal Tahun Ajaran 2021/2022 - Mahmudah, Isnaeni; Darmawan, Agus (Universitas Negeri Semarang, 2023)
This study aims to know the difficulty level in learning front rolling gymnastics at the Dabin Talang in Tegal regency in the academic year 2021/2022. This research was a quantitative research using a survey method and questionnaire as the instrument. The population of the research was elementary students at the Dabin Talang in the academic years 2021/2022. The sample group was taken using cluster random sampling; there were 140 respondents in this study. The collecting data were analysed using statistical analyses technic with percentages. The result of this study showed that the level of difficulty in learning front rolling floor gymnastics were (11.4%) very low, (23.6%) low, (37.9%) medium, and (1.4%) very high. In coclusion, the difficulty level in learning front rolling floor gymnastics at DabinTalang in the academic year 2021/2022 was high (37.9%) because of internal and external factors.